2007
DOI: 10.1073/pnas.0705320104
|View full text |Cite
|
Sign up to set email alerts
|

Reticular nucleus-specific changes in α3 subunit protein at GABA synapses in genetically epilepsy-prone rats

Abstract: Differential composition of GABAA receptor (GABAAR) subunits underlies the variability of fast inhibitory synaptic transmission; alteration of specific GABAAR subunits in localized brain regions may contribute to abnormal brain states such as absence epilepsy. We combined immunocytochemistry and high-resolution ImmunoGold electron microscopy to study cellular and subcellular localization of GABA AR ␣1, ␣3, and ␤2/␤3 subunits in ventral posterior nucleus (VP) and reticular nucleus (RTN) of control rats and WAG/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…There are also similarities with some differences between the 3 strains as far as the mechanisms of SWDs. It has been demonstrated, that (i) several neurotransmitter systems are involved in the pathophysiological processes leading to absence epileptic seizures and their maintenance/recurrence such as glutamatergic system, GABAergic system, dopaminergic and nucleosiderg system in GAERS rats, WAG/Rij rats and Long Evans rats (Bazyan and Van Luijtelaar, 2013;Depaulis and Van Luijtelaar, 2005;Kovács et al, 2013Kovács et al, , 2014Li et al, 2006;Polack and Charpier, 2006), (ii) the effects of anti-epileptic drugs on SWDs were similar in GAERS rats, WAG/Rij rats and Long Evans rats (e.g., ethosuximide, and valproate decreased the number of SWDs) (Chen et al, 2011;Depaulis and Van Luijtelaar, 2005;Shaw, 2004Shaw, , 2007, (iii) sodium channel (Nav1.1 and Nav1.6) expression was selectively increased in the somatosensory cortex of WAG/Rij rats in relation to age-dependent increase in seizure number and duration (Klein et al, 2004), (iv) selective decrease in thalamic (e.g., reticular thalamic nucleus) and cortical (e.g., somatosensory cortex) GABA (A) receptor subunits such as reduction of ␣3 subunit of GABA (A) receptor in reticular thalamic nucleus of WAG/Rij rats (Liu et al, 2007) may have a role in the pathophysiology of absence epilepsy in Long Evans rats, WAG/Rij rats and GAERS rats (Li et al, 2006;Spreafico et al, 1993), (v) mRNA levels for most GABA (B(1)) subunits were lower in WAG/Rij neocortex than in cortex of control nonepileptic rats, which can contribute to neocortical hyperexcitability and SWD generation (Merlo et al, 2007) whereas GABA (B(1)) subunit mRNA levels were higher and lower in the somatosensory cortex and ventrobasal thalamic nuclei of GAERS rats, respectively, compared with control animals (Princivalle et al, 2003), (vi) decreased alpha-amino-3-hydroxy-5-methyl-4-isoazolepropionic acid receptor (AMPA; AMPA-GluR4) and N-methyl-d-aspartate receptor (NMDA; NMDA-NR1) expression in the cortical focus of WAG/Rij animals (compared with non-epileptic control rats) and increased AMPA-GluR1/2 expression in GAERS rats in the somatosensory cortex may be in relation to hyperexcitability in somatosensory cortex and to SWD initiation (Van de BovenkampJanssen et al, 2006;Kennard et al, 2011), (vii) reduction of group-I metabotropic glutamate receptors (mGlu1 receptors) in ventrobasal thalamic nuclei and increased expression of group-II metabotropic glutamate receptors (mGlu2/3 receptors) in WAG/Rij rat somatosensory cortex and ventrobasal thalamic nuclei may be involved in the ge...…”
Section: Discussionmentioning
confidence: 96%
“…There are also similarities with some differences between the 3 strains as far as the mechanisms of SWDs. It has been demonstrated, that (i) several neurotransmitter systems are involved in the pathophysiological processes leading to absence epileptic seizures and their maintenance/recurrence such as glutamatergic system, GABAergic system, dopaminergic and nucleosiderg system in GAERS rats, WAG/Rij rats and Long Evans rats (Bazyan and Van Luijtelaar, 2013;Depaulis and Van Luijtelaar, 2005;Kovács et al, 2013Kovács et al, , 2014Li et al, 2006;Polack and Charpier, 2006), (ii) the effects of anti-epileptic drugs on SWDs were similar in GAERS rats, WAG/Rij rats and Long Evans rats (e.g., ethosuximide, and valproate decreased the number of SWDs) (Chen et al, 2011;Depaulis and Van Luijtelaar, 2005;Shaw, 2004Shaw, , 2007, (iii) sodium channel (Nav1.1 and Nav1.6) expression was selectively increased in the somatosensory cortex of WAG/Rij rats in relation to age-dependent increase in seizure number and duration (Klein et al, 2004), (iv) selective decrease in thalamic (e.g., reticular thalamic nucleus) and cortical (e.g., somatosensory cortex) GABA (A) receptor subunits such as reduction of ␣3 subunit of GABA (A) receptor in reticular thalamic nucleus of WAG/Rij rats (Liu et al, 2007) may have a role in the pathophysiology of absence epilepsy in Long Evans rats, WAG/Rij rats and GAERS rats (Li et al, 2006;Spreafico et al, 1993), (v) mRNA levels for most GABA (B(1)) subunits were lower in WAG/Rij neocortex than in cortex of control nonepileptic rats, which can contribute to neocortical hyperexcitability and SWD generation (Merlo et al, 2007) whereas GABA (B(1)) subunit mRNA levels were higher and lower in the somatosensory cortex and ventrobasal thalamic nuclei of GAERS rats, respectively, compared with control animals (Princivalle et al, 2003), (vi) decreased alpha-amino-3-hydroxy-5-methyl-4-isoazolepropionic acid receptor (AMPA; AMPA-GluR4) and N-methyl-d-aspartate receptor (NMDA; NMDA-NR1) expression in the cortical focus of WAG/Rij animals (compared with non-epileptic control rats) and increased AMPA-GluR1/2 expression in GAERS rats in the somatosensory cortex may be in relation to hyperexcitability in somatosensory cortex and to SWD initiation (Van de BovenkampJanssen et al, 2006;Kennard et al, 2011), (vii) reduction of group-I metabotropic glutamate receptors (mGlu1 receptors) in ventrobasal thalamic nuclei and increased expression of group-II metabotropic glutamate receptors (mGlu2/3 receptors) in WAG/Rij rat somatosensory cortex and ventrobasal thalamic nuclei may be involved in the ge...…”
Section: Discussionmentioning
confidence: 96%
“…It is known that RTN is characterized by a pattern of collaterals establishing axodendritic, somatodendritic, and dendrodendritic synapses within the RTN (Csillik et al 2005;Spreafico et al 1991;Steriade et al 1984;Yingling and Skinner 1976). These collaterals are GABAergic, expressing GABA(␤3) as opposed to the RTN projections onto the thalamocortical (TC) cells that express GABA(␤3) (Liu et al 2007;Sohal and Huguenard 2003). Recent findings have shown that these collateral synapses within RTN are likely to be much weaker than the RTN-TC synapses (Lam et al 2006).…”
Section: Functional Connectivity Of Rtn Neurons Is Unchanged In Pvko mentioning
confidence: 99%
“…Human absence epilepsy is associated with mutations in the genes encoding the  5 ,  3 , or  2 subunits of the GABA A receptor (Hirose, 2014) and the amount of the  3 subunit in the NRT has been shown to be reduced in WAG/Rij rats as compared to non-epileptic control rats (Gauguier et al, 2004;Liu et al, 2007); instead, GABA A receptors are preserved in the neocortex of WAG/Rij epileptic rats, which are defective in several GABA B receptor isoforms (Liu et al, 2007;Merlo et al, 2007).…”
Section: Gabamentioning
confidence: 99%